Development of Teaching Materials Assisted by the Kvisoft Flipbook Maker Application to Improve Students Critical Thinking Skills - Muhammadi Muhammadi; Niki Yulianti (Jurnal Penelitian Pendidikan IPA, 2023)
The PBL approach must be used in the creation of instructional materials for class III primary schools, utilizing the Kvisoft Flipbook Maker application. This study employs a new design for development research, or R&D, which proceeds through the following processes to arrive at the ADDIE model: analysis, design, development, implementation, and evaluation. Students in class III at SDN 01 Campago, SDN 03 Limo Badak, and SDN 10 Sasai Kandang in the Malalak District of the Agam Regency served as the research subjects. The results obtained from the standard validity analysis were "very valid" with an average media expert assessment of 91. 8%, material expert assessment 90.175% and language expert assessment 83.33%. From the practicality testing, educators received an assessment of 95.27% with the criteria "very practical". In summary, the creation and application of instructional materials utilizing the PBL paradigm in class III elementary schools, based on the Kvisfot flipbook maker program, satisfies the requirements for validity, practicality, and effectiveness.